2020
DOI: 10.1039/d0tc03690k
|View full text |Cite
|
Sign up to set email alerts
|

Ion diffusion coefficients in poly(3-alkylthiophenes) for energy conversion and biosensing: role of side-chain length and microstructure

Abstract: Electrochemically deposited conductive polymers, with their ion imprinted channels, can increase ion transport speed by three orders of magnitude over their spin coated counterparts by eliminating energetic traps for ion movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…This occurs because the crystalline regions are doped at lower oxidation voltages compared to the amorphous ones, so that the unstructured signature of amorphous neutral P3HT persists at more negative voltages. 20,21,56,57 The polaron component (shown in green in Figure 3b) peaks at ~780 nm (P2 band), and has a second transition (P1 band) rising above 1200 nm. 23,57,58 The bipolarons (blue spectrum) absorb at wavelengths longer than 900 nm with a peak at 1350 nm.…”
Section: Resultsmentioning
confidence: 99%
“…This occurs because the crystalline regions are doped at lower oxidation voltages compared to the amorphous ones, so that the unstructured signature of amorphous neutral P3HT persists at more negative voltages. 20,21,56,57 The polaron component (shown in green in Figure 3b) peaks at ~780 nm (P2 band), and has a second transition (P1 band) rising above 1200 nm. 23,57,58 The bipolarons (blue spectrum) absorb at wavelengths longer than 900 nm with a peak at 1350 nm.…”
Section: Resultsmentioning
confidence: 99%
“…These two factors are critical for biological studies, which require a large number of devices. Furthermore, rr-P3HT is considered the prototypical organic electronic material and as such, the electrochemical properties have been highly characterized. ,, The oxidation potential is such that a number of small molecules, common redox probes, can be utilized with systematic variation in the formal potential. We then repeated the measurements using a second polymer, PBTTT-C12, which exhibits a greater degree of structural ordering and orientation, resulting in a higher carrier mobility and volumetric capacitance compared to P3HT in our electrolyte. The estimation of the DOS for organic semiconducting polymers has been previously described ,, and is summarized in Supplemental Note 2 in the Supporting Information section with corresponding calculations from Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, rr-P3HT is considered the prototypical organic electronic material and as such, the electrochemical properties have been highly characterized. 32,34,51 The oxidation potential is such that a number of small molecules, common redox probes, can be utilized with systematic variation in the formal potential. We then repeated the measurements using a second polymer, PBTTT-C12, which exhibits a greater degree of structural ordering and orientation, resulting in a higher carrier mobility and volumetric capacitance compared to P3HT in our electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Across the OMIEC literature, a broad suite of active materials has been reported with varying extents of solid-state order and crystallinity. While a number of OMIECs exhibit substantial solid-state order (especially those used in OECT applications ,, ), there also exist many high-performing active materials that show little to no long-range order. In fact, studies have found that greater crystallinity and/or long-range ordering of the π system is not de facto beneficial for performance, especially considering how disordered systems tend to facilitate ion transport. ,,, In addition, OMIECs prepared by electropolymerization (which is a commonly used route, especially for electrochemical supercapacitors) tend to be very disordered. With these examples in mind, we believe that understanding the properties of disordered systems (like ProDOT­(OE 3 )-DMP) is crucial for the development of the field.…”
Section: Discussionmentioning
confidence: 99%
“…74−76 In fact, studies have found that greater crystallinity and/or longrange ordering of the π system is not de facto beneficial for performance, especially considering how disordered systems tend to facilitate ion transport. 30,36,77,78 In addition, OMIECs prepared by electropolymerization (which is a commonly used route, especially for electrochemical supercapacitors 79 ) tend to be very disordered. With these examples in mind, we believe that understanding the properties of disordered systems (like ProDOT(OE 3 )-DMP) is crucial for the development of the field.…”
Section: ■ Conclusionmentioning
confidence: 99%